Effect of Integrated crop management and blackgram (Vigna mungo) intercropping in maize (Zea mays) - T, VARATHARAJAN; DASS, ANCHAL; CHOUDHARY, ANIL K; POONIYA, V; DAS, T K; PRASAD, SHIV; BISWAS, D R; K, SWARNALAKSHMI; N, HARISH M (The Indian Journal of Agricultural Sciences, 2022)
A 2 year field experiment was conducted during rainy (kharif) seasons of 2019 and 2020 to investigate the influence of integrated crop management (ICM) modules and blackgram (Vigna mungo L.) intercropping on crop growth, productivity and crop efficiencies in maize (Zea mays L.). The maize crop under ICM7 [zero-tillage (ZT) + permanent raised-beds (PRB) + crop residue retention (3 t/ha) + 100% RDF + glyphosate pre-planting (PP) followed by (fb) pendimethalin pre-emergence (PE) fb tembotrione post-emergence (POE) application + 3 irrigations + need-based integrated crop protection] module intercropped with blackgram showed significantly higher plant height, dry matter accumulation (174.2 g/plant), crop growth rate (20.8 g/m2/day), relative growth rate (115 mg/g/day), average grain (6.17 t/ha), and stover yield (8.2 t/ha) and average crop efficiencies like production (60.2 kg/ha/day), monetary-efficiency (795.5 `/ha/day) and irrigation water productivity (4 kg/m3) over conventional-till and organic module in both study years. Overall, conservation agriculture (CA)-based module involving zero-tillage on PRB, crop residue retention, 100% RDF, glyphosate-PP, pendimethalin-PE and tembotrione-POE with 3-irrigations and other need-based plant protection measures with blackgram intercropping improved growth, yield and crop efficiencies of maize under maize + blackgram-wheat cropping system.